-5x(3-2x)=4

Simple and best practice solution for -5x(3-2x)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x(3-2x)=4 equation:


Simplifying
-5x(3 + -2x) = 4
(3 * -5x + -2x * -5x) = 4
(-15x + 10x2) = 4

Solving
-15x + 10x2 = 4

Solving for variable 'x'.

Reorder the terms:
-4 + -15x + 10x2 = 4 + -4

Combine like terms: 4 + -4 = 0
-4 + -15x + 10x2 = 0

Begin completing the square.  Divide all terms by
10 the coefficient of the squared term: 

Divide each side by '10'.
-0.4 + -1.5x + x2 = 0.0

Move the constant term to the right:

Add '0.4' to each side of the equation.
-0.4 + -1.5x + 0.4 + x2 = 0.0 + 0.4

Reorder the terms:
-0.4 + 0.4 + -1.5x + x2 = 0.0 + 0.4

Combine like terms: -0.4 + 0.4 = 0.0
0.0 + -1.5x + x2 = 0.0 + 0.4
-1.5x + x2 = 0.0 + 0.4

Combine like terms: 0.0 + 0.4 = 0.4
-1.5x + x2 = 0.4

The x term is -1.5x.  Take half its coefficient (-0.75).
Square it (0.5625) and add it to both sides.

Add '0.5625' to each side of the equation.
-1.5x + 0.5625 + x2 = 0.4 + 0.5625

Reorder the terms:
0.5625 + -1.5x + x2 = 0.4 + 0.5625

Combine like terms: 0.4 + 0.5625 = 0.9625
0.5625 + -1.5x + x2 = 0.9625

Factor a perfect square on the left side:
(x + -0.75)(x + -0.75) = 0.9625

Calculate the square root of the right side: 0.981070844

Break this problem into two subproblems by setting 
(x + -0.75) equal to 0.981070844 and -0.981070844.

Subproblem 1

x + -0.75 = 0.981070844 Simplifying x + -0.75 = 0.981070844 Reorder the terms: -0.75 + x = 0.981070844 Solving -0.75 + x = 0.981070844 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.75' to each side of the equation. -0.75 + 0.75 + x = 0.981070844 + 0.75 Combine like terms: -0.75 + 0.75 = 0.00 0.00 + x = 0.981070844 + 0.75 x = 0.981070844 + 0.75 Combine like terms: 0.981070844 + 0.75 = 1.731070844 x = 1.731070844 Simplifying x = 1.731070844

Subproblem 2

x + -0.75 = -0.981070844 Simplifying x + -0.75 = -0.981070844 Reorder the terms: -0.75 + x = -0.981070844 Solving -0.75 + x = -0.981070844 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.75' to each side of the equation. -0.75 + 0.75 + x = -0.981070844 + 0.75 Combine like terms: -0.75 + 0.75 = 0.00 0.00 + x = -0.981070844 + 0.75 x = -0.981070844 + 0.75 Combine like terms: -0.981070844 + 0.75 = -0.231070844 x = -0.231070844 Simplifying x = -0.231070844

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.731070844, -0.231070844}

See similar equations:

| 2(7e-8)=40 | | 3x-2(-2)=13 | | 3(2+-0.5y)-2y=13 | | -4*7= | | 7(3+b)=-70 | | 8*3*4= | | -2(2a+3)=-6 | | (17-12)(19-9)(7-4)= | | -2(2a-3)=34 | | (17-12)*(19-9)*(7-4)= | | 7z-15=-15+4z | | 1+0.5y+y=7 | | 5n+11=-2+1 | | 4(2x-5)=3(2x+8) | | 3y-2=7 | | 3x^2+kx-18=0 | | 2y^2+6y+9=0 | | 2x+8y=1 | | -5(3x+7)=10 | | 8x^2+73x+70=0 | | 8x^2-73x-70=0 | | 7(c+4)=21 | | 10*10=x*4 | | 8x^2+73x-70=0 | | 15*16=12*x | | 8x^2-73x+70=0 | | 3*13=x*9 | | 15*10=x*5 | | 64*60= | | 3+2x+4X^2=0 | | 48*64= | | 60*80=eh*fh |

Equations solver categories